2022
DOI: 10.3390/children9111652
|View full text |Cite
|
Sign up to set email alerts
|

A Videogame as a Tool for Clinical Screening of Possible Vulnerability to Impulsivity and Attention Disturbances in Children

Abstract: An attention disturbance is a problem that affects many school-aged children. The assessment in children is usually report-based, and as a result, controversy surrounds the diagnosis. To solve this issue, the aim of this study was to develop a new tool to detect possible attention-related problems and impulsive behavior in 4- and 5-year-old children. This tool was developed as an Android app and could be used to provide an early indicator of possible future development problems. A sample of 103 children (48 gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 54 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…They found that sign-tracking was associated with attentional and inhibitory control deficits and that ST overly relied on subcortical cue-reactive brain systems. Despite not investigating ST/GT per se, Serrano-Barroso et al [37] used an gamified autoshaping task in a sample of 103 young children, and found a relationship between high and low respondents on the task and level of attention, indicating that the tool might help evaluate endophenotypes and link them to attentional problems.…”
Section: Introductionmentioning
confidence: 99%
“…They found that sign-tracking was associated with attentional and inhibitory control deficits and that ST overly relied on subcortical cue-reactive brain systems. Despite not investigating ST/GT per se, Serrano-Barroso et al [37] used an gamified autoshaping task in a sample of 103 young children, and found a relationship between high and low respondents on the task and level of attention, indicating that the tool might help evaluate endophenotypes and link them to attentional problems.…”
Section: Introductionmentioning
confidence: 99%